If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4+n=-2n+3n
We move all terms to the left:
4+n-(-2n+3n)=0
We add all the numbers together, and all the variables
n-(+n)+4=0
We get rid of parentheses
n-n+4=0
We add all the numbers together, and all the variables
4!=0
There is no solution for this equation
| 2x-3x+5x+9(x+2)=50.5 | | /2x-3x+5x+9(x+2)=50.5 | | 7x^2-19x-15.5=0 | | 2u+5.5=16.3 | | 2n+2=-3-3n | | 391-2n=33 | | 6-3n=n+2 | | 4(t-3)+4=4(2t-4) | | 4x2+3=−3x | | -2(n+3)-1=-1+n | | -2(n+3)-1=-1 | | 6(x-2)/2=3(x+9)/2 | | ¼y=-4½ | | 3n+40=61 | | 27=x/4+8 | | 19.48+y=37.48 | | x-3(3+3x)=-9-2x | | -17x+170/x+11=0 | | 14+x=3(3x+2) | | ^2+12x=-25 | | y-8/2=9 | | -6+2m=-3(3m+2) | | 7z−4=52 | | 9(5y=36) | | 16x-14=9x-7 | | 5x-3(1-7x)=205 | | 3(x+4)+2=6x-3(-4+x) | | 5t-5=9t+5 | | -4(-5r+2)+1=-107 | | (6x+3)+(7x-19)=180 | | 7(5+7x)-4=-263 | | -2(5p+8)=-86 |